An experimental and CFD investigation into the mixing in a closed system stirred vessel. (2014) - Thompson, Jennifer; McBride, Diane; Wilson, Benjamin P.; Hassan, Oubay; Plummer, Sue; Bould, David; Rolland, Sam; Lavery, Nick; Sienz, Hans
No abstract available